Analytische Losungen einer Klasse der Differentialgleichungen der ersten Ordnung - Kisielius, J. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. В. Киселюс. Аналитические решения одного класса дифференциальных уравнений первого порядка J. Kisielius. Vienos pirmos eilės diferencialinių lygčių klasės analiziniai sprendiniai